In Vivo Cannabidiol Treatment Improves Endothelium-Dependent Vasorelaxation in Mesenteric Arteries of Zucker Diabetic Fatty Rats - Wheal, Amanda J.; Jadoon, Khalid; Randall, Michael D.; O’Sullivan, Saoirse E. (Frontiers in Pharmacology, 2017)
Background and purpose. We have shown that in vitro treatment with cannabidiol (CBD, 2 h) enhances endothelial function in arteries from Zucker Diabetic Fatty (ZDF) rats, partly due to a cyclooxygenase (COX)-mediated mechanism. The aim of the present study was to determine whether treatment with CBD in vivo would also enhance endothelial function. Experimental approach. Male ZDF rats, or ZDF Lean rats, were treated for 7 days (daily i.p. injection) with either 10mg/kg CBD or vehicle (n=6 per group). Sections of mesenteric resistance arteries, femoral arteries and thoracic aortae were mounted on a wire myograph, and cumulative concentration-response curves to endothelium-dependent (acetylcholine, ACh, 1nM-100M) or endothelium-independent (sodium nitroprusside, SNP, 1nM-100M) agents were constructed. Multiplex analysis was used to measure serum metabolic and cardiovascular biomarkers. Key results. Vasorelaxation to ACh was significantly enhanced in mesenteric arteries from CBD-treated ZDF rats, but not ZDF Lean rats. The enhanced vasorelaxation in ZDF mesenteric arteries was no longer observed after COX inhibition using indomethacin or nitric oxide (NO) inhibition using L-NAME. Increased levels of serum c-peptide, insulin and intracellular adhesion molecule 1 (iCAM) observed in the ZDF compared to ZDF Lean rats were no longer significant after 7 days CBD treatment. Conclusions and implications. Short-term in vivo treatment with CBD improves ex vivo endothelium-dependent vasorelaxation in mesenteric arteries from ZDF rats due to COX- or NO-mediated mechanisms, and leads to improvements in serum biomarkers.